Mexican oregano essential oils given in drinking water on performance, carcass traits, and meat quality of broilers - Hernández Coronado, Ana Cecilia; Silva Vázquez, Ramón; Rangel Nava, Zayd Eliud; Hernández Martínez, Carlos Alberto; Kawas Garza, Jorge Ramsy; Hume, Michael E.; Méndez Zamora, Gerardo (Poultry Science Association, 2019)
The objective of this study was to evaluate the effects of 2 Mexican oregano essential oils (MOO), from Poliomintha longiflora Gray (PLG) and Lippia berlandieri Schauer (LBS), in drinking water (DWt) on the performance, slaughter variables, and meat quality of broilers over a 40 D period of growth. A total of 180 non-sexed Ross-308 broilers (1-day-old) were randomly assigned to 3 treatments with 6 replications each (10 birds per replicate): CON = DWt control (without MOO); PLG = DWt + 400 mg/L of PLG; and LBS = DWt + 400 mg/L of LBS. The CON, PLG, and LBS broilers body weights were similar (P > 0.05) at all times. Feed intake (FI) was different by treatment (P < 0.05) at 7 and 28 D, and water intake (WI) was different (P < 0.05) at day 28. The CON treatment was highest (P < 0.05) at 28 D for FI and WI, whereas LBS was lowest (P < 0.05). Weight gain (WG) for CON, PLG, and LBS broilers was similar (P > 0.05), although WG for CON was slightly higher. In CON broilers, slaughter weight was highest (P < 0.05), but thigh yield was lowest (P < 0.05). The CON and PLG treatments were lower (P < 0.05) in thigh and leg cooking losses. The PLG treatment presented the highest values (P < 0.05) for breast-meat redness, saturation index, shear force, odor, taste, and overall sensory acceptability. The LBS was higher (P < 0.05) for breast-meat shear force, cohesiveness and resilience, but lower (P <0.05) for sensory attributes. Mexican oregano essential oils at 400 mg/L can serve as natural alternative additives in DWt to improve broiler production and meat quality.